Turnover Intention in Public Accountant Firms of East Java - I Putu Hendra Setiawan; Nurkholis Nurkholis; Bambang Hariadi (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2019)
This research aims to investigate empirically the influence of pay satisfaction, role conflict and role ambiguity on auditor turnover intention, which are mediated by job satisfaction. A number of 168 auditors who work for Public Accounting Firms in East Java participated in this research. The data is analyzed using PLS (Partial Least Squares). The result shows that pay satisfaction positively influences job satisfaction and negatively influences auditors’ turnover intention. Role conflict does not have any direct influence to job satisfaction but has a direct positive influence toward turnover intention. Role Ambiguity positively influences job satisfaction and negatively influences auditors’ turnover intention. Besides, this research also reveals that job satisfaction has a partial mediation effect between pay satisfaction and auditors’ turnover intention and has a full mediation effect between role ambiguity and auditors’ turnover intention, but it has no mediation effect between role conflict and auditors’ turnover intention.